EKSPLORASI BRAND LOYALTY PADA LEMBAGA KEUANGAN NON-BANK: PERSPEKTIF ANGGOTA KOPERASI SIMPAN PINJAM BALO’ TORAJA - Mursyid, Mursyid; Nurherlina, Nurherlina; Isdayanti, Isdayanti (ITB AAS Indonesia Surakarta, 2024)
Brand loyalty is one of the important components in maintaining the competitive advantage and sustainability of non-bank financial institutions. This study aims to determine brand loyalty in the Balo' Toraja Savings and Loan Cooperative and explore the factors that shape it from the perspective of members. The research method used is a qualitative method with an exploratory approach through in-depth interviews. The results of the study show that the members of the Balo' Toraja Savings and Loan Cooperative have a high brand loyalty, which is formed through brand trust, brand satisfaction, service quality, perception of quality, and local wisdom. Brand trust and brand satisfaction are the main factors in building brand loyalty, as indicated by the long-term commitment of members to remain part of the cooperative. In addition, good service quality and perception of quality are drivers of the formation of member brand loyalty. The local wisdom values owned by the Balo' Toraja Savings and Loan Cooperative form a strong emotional bond, thus supporting the formation of member loyalty to the Balo'ta brand. Keywords : brand loyalty, cooperatives, brand trust, brand satisfaction, service quality, perception of quality, local wisdom.